De falcone Bartolusa de Saxoferrato - Kaczmarczyk, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Among the numerous texts by the famous Italian jurist Bartolus de Saxoferrato there is a short letter entitled tractatus de falcone — treaty of the falcon. Despite its name, it is neither a work about the issue of hunting with birds of prey, nor a letter exhausting the literary form of a treaty. Although Diplovatatius described it as consilium, it should be rather classified as quaestiones.It should be emphasized that the distinction of consilium, that is a legal advice drew up to consider the specific case from quaestio, theoretical analysis of some case, may be impossible. The more so that the basis for quaestiones were often genuine judicial cases, which were only changed with regards to identifying the parties and adjusting the case to the needs of teaching. The author made a translation of de falcone and added her own commentary.
Keywords: Bartolus de Saxoferrato (1313-1357)